The role of expatriates in intellectual and political life in Najaf in the twentieth century (Journal of the College of Basic Education, 2023)
For nearly a thousand years, the city of Najaf has been a pioneering scientific center that students of religious sciences from all over the world come to to study in its scientific seminary. And they grew up in it until they became like its children, and the city of Najaf, which has a religious and cultural character, has a charm and influence even on the incoming students who are in the age of youth and maturity. And the original inhabitants of Najaf came the idea of ​​research.